The exchange rate exposure of UK non-financial companies. - El-Masry, A.; Abdelsalam, O.; Alatraby, A. (Managerial Finance, 2007)
Purpose – The purpose of this paper is to investigate the exchange rate exposure of UK non‐financial companies from January 1981 to December 2001. Design/methodology/approach – The study employs different exchange rate measures and adopts an equally weighted exchange rate. The analyses are conducted at the firm level. All analyses are conducted by regressing the firm's exchange rate exposure coefficients on its size, foreign activity variables and financial hedging proxies over the whole sample period. Findings – The findings show that a higher percentage of UK non‐financial companies are exposed to exchange rate changes than those reported in previous studies. Generally, the results provide a stronger support for the suggested equally weighted rate as an economic variable, which affects firms’ stock returns. The results also show a high proportion of positive exposure coefficients among firms with significant exchange rate exposure, indicating a higher proportion of firms benefiting from an appreciation of the pound. Finally, the results also indicate evidence that firms’ foreign operations and hedging variables affect their sensitivity to exchange rate exposure. Practical implications – This study provides important implications for public policymakers who wish to understand links between policies that affect exchange rates and relative wealth effects. Originality/value – The empirical results of this study should help investors to examine how common stock returns react to exchange rate fluctuations when making financial decisions, and prove useful for financial managers when measuring exposure to foreign exchange rate changes.
Keywords: Exchange rates; Exchange rate mechanisms; Companies; Value analysis.